2008
DOI: 10.1088/1742-6596/103/1/012007
|View full text |Cite
|
Sign up to set email alerts
|

Noncommutative induced gauge theories on Moyal spaces

Abstract: Noncommutative field theories on Moyal spaces can be conveniently handled within a framework of noncommutative geometry. Several renormalisable matter field theories that are now identified are briefly reviewed. The construction of renormalisable gauge theories on these noncommutative Moyal spaces, which remains so far a challenging problem, is then closely examined. The computation in 4-D of the one-loop effective gauge theory generated from the integration over a scalar field appearing in a renormalisable th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 47 publications
(121 reference statements)
0
42
0
Order By: Relevance
“…In the present paper, we consider as in [55] the differential calculus generated by the Lie algebra of real inner derivations of R 3 12) where the inner derivation D µ satisfy the following commutation relation 15) where the X i 's are elements of G and |σ| is the signature of the permutation σ ∈ S p+q . Let M denotes a right-module over R 3 λ .…”
Section: Jhep12(2015)045mentioning
confidence: 99%
See 1 more Smart Citation
“…In the present paper, we consider as in [55] the differential calculus generated by the Lie algebra of real inner derivations of R 3 12) where the inner derivation D µ satisfy the following commutation relation 15) where the X i 's are elements of G and |σ| is the signature of the permutation σ ∈ S p+q . Let M denotes a right-module over R 3 λ .…”
Section: Jhep12(2015)045mentioning
confidence: 99%
“…NCFT on noncommutative Moyal spaces received a lot of attention from the end of the 90's, in particular from the viewpoint of perturbative properties and renormalisability [10][11][12]. For reviews, see for instance [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Some detailed studies of the Moyal NC algebra are carried out e.g in [8,9] while mathematical descriptions of the NC framework underlying the present study can be found in [37,21].…”
Section: Basic Featuresmentioning
confidence: 99%
“…Here, A µ denotes the so called covariant coordinates defined in section 2, a natural gauge covariant tensorial form stemming from the existence of a canonical gauge invariant connection within the present NC framework (for more details on the relevant mathematical structures see e.g in [36,37,21]. In (1.2), the additional 2nd term may be viewed as a "gauge counterpart" of the harmonic term introduced in [15].…”
mentioning
confidence: 99%
“…Once the noncommutative nature of space-time is assumed which is generally reflected into the noncommutativity of an algebra of coordinates, noncommutative field theories (NCFT) or noncommutative gauge theories naturally arise. For reviews on early studies, see e.g [10][11][12] and references therein.…”
Section: Introductionmentioning
confidence: 99%